Prebiotic Chemistry: The Role of Trimetaphosphate in Prebiotic Chemical Evolution - Gan, Dingwei; Ying, Jianxi; Zhao, Yufen (Frontiers in Chemistry, 2022)
Life’s origins have always been a scientific puzzle. Understanding the production of biomolecules is crucial for understanding the evolution of life on Earth. Numerous studies on trimetaphosphate have been conducted in the field of prebiotic chemistry. However, its role in prebiotic chemistry has been documented infrequently in the review literature. The goal of this thesis is to review the role of trimetaphosphate in the early Earth’s biomolecule synthesis and phosphorylation. Additionally, various trimetaphosphate-mediated reaction pathways are discussed, as well as the role of trimetaphosphate in prebiotic chemistry. Finally, in our opinion, interactions between biomolecules should be considered in prebiotic synthesis scenarios since this may result in some advances in subsequent research on this subject. The research establishes an essential and opportune foundation for an in-depth examination of the “mystery of life".